Climate Long-Term Trends Impacting Wheat Production Systems in Kansas - Octavia M.M. Tavares; Fábio Marin; Romulo Lollato; Bruno C. Pedreira (Kansas Agricultural Experiment Station Research Reports, 2023)
Winter wheat production is of major importance in Kansas. The purpose of the study was to verify the evidence of climate change in a long-term weather data series from Wellington and Parsons, KS, to understand whether climate change has been affecting yield production.
Keywords: climate change; cropping systems; temperature; weather